BENCANA: KESALAHAN MANUSIA ATAU RENCANA ALLAH? (Perspektif Filsafat Ketuhanan) - Donatus Sermada Kelen (Litbang STFT Widya Sasana Malang, 2005)
Every catastrophe either the natural one, disease or that caused by the cruel human acts, shows a cosmic power. It follows the natural law. Speaking catastrophes caused by human faults or God’s plan, we however should reflect and interpret it in metaphysical assumptions. The problems of evil manifesting in the natural catastrophes and in the evil doings of human being are relevant to be discussed in order to find out what kind of metaphysical assumption is implied in the certain reflection and interpretation of such problems. The problems are often set against the faith of the existence of God. So, either the Theodicists or the anti-theodicists propose their own argumentations. In the last part the author tries to introduce a cosmology of post-modernism which leads us into a new insight to reflect and to interpret whether the catastrophe comes out due to the faults of human being or to the plan of God